2018
DOI: 10.1142/s2424835518500091
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Intramedullary Fixation for Distal Radius Fractures in Elderly Patients: A Retrospective Analysis Using McKay’s Complication Checklist

Abstract: Intramedullary fixation for distal radius fractures was free from tendinous complications such as tenosynovitis and tendon ruptures around the implant, which are frequently caused by volar locking plate fixation. However, this less invasive technique could not avoid common complications such as trigger finger and carpal tunnel syndrome associated with distal radius fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A significantly higher incidence of implant-related complications may, at least partially account for the lower satisfaction in the plate group. Surgical complications of intramedullary nail fixation may include dorsal superficial radial sensory nerve injury and potentially suboptimal reduction due to inadequate surgical exposure [25]. Higher percentage of transient paresthesia in the nail group should caution the surgeon to aim for a more meticulous soft tissue and to protect the nerve during surgical dissection.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher incidence of implant-related complications may, at least partially account for the lower satisfaction in the plate group. Surgical complications of intramedullary nail fixation may include dorsal superficial radial sensory nerve injury and potentially suboptimal reduction due to inadequate surgical exposure [25]. Higher percentage of transient paresthesia in the nail group should caution the surgeon to aim for a more meticulous soft tissue and to protect the nerve during surgical dissection.…”
Section: Discussionmentioning
confidence: 99%
“…According to this study, 1.6% extensor tenosynovitis, 1% extensor tendon rupture, 0.7% flexor tendon rupture, 0.7% flexor tendon tenosynovitis, 0.7% loss of screw fixation, 0.3% lunate facet loss loss, 0.3% distal radioulnar joint injury with screws 0.3% median nerve damage, 0.3% infection complications. One study reported that although intramedullary fixation of the distal radius fractures was less invasive, the patient could not avoid common complications such as trigger finger and carpal tunnel syndrome [26]. Similarly, in another study, it was reported that the results of volar locking plate and intramedullary fixation were similar and both techniques did not reduce postoperative complications [27].…”
Section: Akalın Y Et Al Distal Radius Intraarticular Fracturesmentioning
confidence: 99%